2011
DOI: 10.1007/s11418-011-0592-0
|View full text |Cite
|
Sign up to set email alerts
|

San-Huang-Xie-Xin-Tang protects cardiomyocytes against hypoxia/reoxygenation injury via inhibition of oxidative stress-induced apoptosis

Abstract: Oxidative stress has been widely implicated in the pathogenesis of hypoxia/reoxygenation (H/R) injury. San-Huang-Xie-Xin-Tang (SHXT), a widely used traditional Chinese medication, has been shown to possess antioxidant effects. Here, we investigated whether SHXT and its main component baicalin can attenuate oxidative stress induced by H/R injury. H9c2 rat ventricular cells were exposed to SHXT or baicalin followed by hypoxia for 24 h and/or reoxygenation for 8 h. Pretreatment with SHXT and baicalin both signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 31 publications
2
29
0
Order By: Relevance
“…Some signaling cascades such as phosphatidylinositol-3-kinase (PI3K) and serine/threonine kinase (Akt) pathways may inhibit CM hypertrophy [7], [8]. The endothelial nitric oxide synthase (eNOS)/nitric oxide (NO) pathway, known as an important factor in regulating vascular function and one of the down-stream of Akt signaling, has also been shown to reduce ROS generation and exert anti-apoptotic effect on CMs [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…Some signaling cascades such as phosphatidylinositol-3-kinase (PI3K) and serine/threonine kinase (Akt) pathways may inhibit CM hypertrophy [7], [8]. The endothelial nitric oxide synthase (eNOS)/nitric oxide (NO) pathway, known as an important factor in regulating vascular function and one of the down-stream of Akt signaling, has also been shown to reduce ROS generation and exert anti-apoptotic effect on CMs [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that this compound exhibits many different pharmacological activities. Baicalin has displayed beneficial effects on several diseases model such as hypoxia/reoxygenation caused cardiomyocytes injury [9], hepatic cytotoxicity [10], iron-overloaded mouse [11], rheumatoid arthritis [12] and so on. Furthermore, recent studies have confirmed the photoprotective effect of baicalin against acute and multiple UVB-induced photodamage [13], [14], [15], [16], and this effect is thought to be associated with reduction of oxidative stress [17].…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, SHSST has been used in East Asia as a representative herbal medicine to treat both hypertension and its complications (Hur, 1613). Recently, scientific studies have newly demonstrated that SHSST has pharmacological efficacy, due to its having anti-inflammatory, anti-oxidative stress, anti-cancer, and neuroprotective properties (Li et al, 2010; Shih et al, 2011; Liou et al, 2012; Lo et al, 2012). These properties would mainly be associated with the constituents of SHSST such as berberine, coptisine, berberastine, worenine, and palmatine from Coptis Rhizome (Manisha, 2009); hydroxyanthracene derivatives (emodin, physcione, aloe-emodin, and chrysophanol glycosides) from Rhei Rhizoma (Manisha, 2009); and aglycones (baicalein, wogonin, oroxylin A) and glycosides (baicalin, wogonoside, oroxylin A-7-glucuronide) from Scutellariae Radix (Li et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…SHSST has traditionally been used in Korea, China, and Japan as a curative for both hypertension and its complications; and it is still widely used for both purposes (Hur, 1613; Jin et al, 2007). According to previous laboratory and clinical studies, SHSST plays a role in the treatment of various diseases including hypertension (Iijima et al, 2000; Lo et al, 2005b; Jin et al, 2007), cardiac disorder (Liou et al, 2012), gastric inflammatory symptoms (Shih et al, 2007), acute lung injury (Lo et al, 2005a), and hepatic disorder (Huang et al, 2011). SHSST also exerts a neuroprotective effect in 6-OHDA-induced toxicity in neuronal SH-SY5Y cells (Shih et al, 2011) and in the MPP(+)/MPTP-induced toxicity, in vitro and in vivo model for Parkinson’s disease (Lo et al, 2012) via its anti-inflammatory, anti-oxidative, and anti-apoptotic activities.…”
Section: Introductionmentioning
confidence: 99%